The analysis of financial performance: the case study for Sri Sutra Travel Sdn Bhd / Noor Hazimah Sain - Sain, Noor Hazimah (Faculty of Business and Management, 2009)
This study reveals on the important of towards having a good financial performance. From that, the analysis on the financial performance will be carried out. The reason is because the stability of one company is depending on their financial performance and how they utilize it for the company benefits. They can operate effectively and efficiently by having good financial performance. From the financial statement (balance sheet and income statement), the evaluation of the company performance can be done. To analyze the company that involve in this study, the basic tool of financial analysis will be used. The financial ratios and common-size analysis will calculated based on the information disclosed on the financial statement of the companies. The study identifies the financial strength on certain criteria. There are five types of common ratios will apply to calculate the financial statement. Each ratios represents the major categories namely liquidity, profitability, operating, asset utilization, and valuation ratio. An analysis has been given on each of the selected ratios after been calculated. From the ratio, we will know the financial performance of the company. The same way goes to common-size analysis, where the way these company managing their assets, liability, and equity were fully analyzed. Thus, the determination whether the company doing well in managing their financial activities in the last 5 years can be made.